Ultrastructure of human platelet concentrates after treatment with pathogen reduction technologies for prolonged storage - Barham, Mohammed; Odenthal, Tobias; Picker, Susanne M.; Grandoch, Andrea; Gathof, Birgit S.; Neiss, Wolfram F. (Frontiers in Medicine, 2025)
Background and objectivesPathogen reduction technologies (PRTs) increase blood supply safety but may also increase platelet storage lesion, probably due to mitochondrial DNA damage. The purpose of this study was to investigate whether these changes are morphologically detectable.Materials and methodsBlood platelets were obtained by triple-dose apheresis collection (n = 8). Immediately after splitting, single units were left untreated (CONTROL) or treated with either psoralen-UVA (INTERCEPT) or riboflavin-UVB (MIRASOL). All platelet units were resuspended in platelet additive solution (INTERSOL or SSP+) and stored for up to seven days. Seven samples from each donation were examined by electron microscopy fresh, i.e., immediately after collection, and after1 day and 7 days of storage either untreated or treated with INTERCEPT or MIRASOL PRT. The volumes of mitochondria and of the canalicular system (CS) were measured.ResultsFreshly isolated platelets (0 days storage) contained 2.4% mitochondria (volume density) and 4.5% CS (volume density). After 1 day of storage mitochondrial volume density was reduced to 1.5% in untreated, 1.3% in INTERCEPT-treated and 1.6% in MIRASOL-treated platelet concentrates, i.e., a loss of up to 37% of mitochondrial volume regardless of treatment. After 7 days storage mitochondrial volume density was 1.3, 1.3 and 1.5% respectively; neither at 1 nor at 7 days storage were any noteworthy differences between untreated, INTERCEPT or MIRASOL-treated platelets. In stark contrast to mitochondria the CS ballooned up to 88% in all groups. After 1 day of storage CS volume density was increased to 8.6% in untreated, 8.4% in INTERCEPT-treated and 7.0% in MIRASOL-treated platelet concentrates. After 7 days storage CS volume density was 8.0, 8.3 and 6.3% respectively; neither at 1 nor at 7 days storage were significant differences between untreated, INTERCEPT or MIRASOL-treated platelets. Only at 7 days a slight tendency of a smaller CS in MIRASOL versus INTERCEPT and untreated CONTROL groups was observed.ConclusionPlatelet mitochondrial volume shrinks and canalicular system swells within the first 24 h after collection and then both remain rather constant for up to seven days with or without PRT treatment. Pathogen reduction technology – both INTERCEPT and MIRASOL – does not increase morphological platelet storage lesion.